Spatial distribution of the annual temperature range in Greece using GIS. - Nastos, P.; Evelpidou, N.; Vassilopoulos, A. (1st Pan-Hellenic Conference: Geographic Information Systems-Capabilities and Applications, Perspectives and Challenges, 1999)
Coastal zone of the Ithaki Island consists mainly of calcareous rocks (>80%) of the Ionian geotectonic zone and secondarily of Neogene sequences, flysch and Quaternary deposits. Due to the presence of carstic limestones, vegetation is poor with the ‘makia’ type of vegetation to cover almost the half of the coastal land. In terms of coast formation, four types of coasts have been identified, according to Shepard’s genetic classification; these are coasts of: tectonic origin, terrestrial deposition, subaerial erosion and marine erosion. The small coastal towns and villages occupy only the 3,1% of the coastal land being developed primarily on Quaternary deposits and in areas with small (10%) topographic slope. Beaches suitable for touristic activities are present within protected small bays and usually are associated with the presence of fluvial deposits reworked by the existed wave activity.